Genetic variation and correlations for some physiological characters and seed yield in Indian mustard (Brassica juncea L.) under rainfed conditions: GENETIC VARIATION IN INDIAN MUSTARD - MAHARAJ SINGH; J S CHAUHAN (Journal of Oilseeds Research, 2013)
An experiment was conducted with 42 Indian mustard genotypes in Randomized Complete Block design to estimate genetic parameters and correlations of some physiological characters and seed yield under rainfed conditions. Specific leaf area, transpiration rate and relative water content were recorded at 30 (vegetative stage), 45-50 (50% flowering stage) and 60-65 days aftersowing (full flowering stage). Total drymatter, harvest index, pod intensity, pod area on main and primary branches, seed : husk ratio and seed yield were recorded at the time of harvest. The analysis of variance indicated highly significant differences among the genotypes for all the characters studied. The maximum phenotypic and genotypic variability was observed for transpiration rate at full flowering stage. Heritability estimates in broad-sense were high for all the characters except relative water contents (RWC) at all the 3 stages, pod area of main and primary branches and pod intensity on main shoot. High heritability combined with high genetic advance was observed for specific leaf area at all the 3 stages, transpiration rate at 50% and fullflowering and total drymatter/plant suggested scope for selection for these characters owing to predominance of additive effects in the expression of these characters. Seed yield/plant had significant and positive correlations with harvest index (r = 0.581**), total drymatter/plant (r = 0.869**), pod intensity on main shoot (r = 0.467**), pod area of main (r = 0.536**) and primary branches ((r = 0.317*) and RWC at all the 3 developmental stages. Thus, selection for high harvest index, total dry matter/plant and pod intensity coupled with low transpiration rate at flowering stage, resulting in maintenance of high RWC in leaves, should be emphasized to increase yield under rainfed conditions.